Evaluate the product/market fit - Molesky, Joanne; Humble, Matthew; O'Reilly, Barry (O'Reilly Media, Inc., 2016)
Evaluating the product and market fit of a solution is critical. Traditional financial accounting measures are not designed for evaluating innovation. Actionable metrics instead need to be applied to evaluate progress and success. Why is it important? Traditional measurement methodologies are skewed to products with a track record of costs and revenues. Innovative products by nature require investment and have little to no revenue and a limited operating history. Using actionable metrics allows you to better evaluate the future adoption and success of a product in your identified market. What you'll learn--and how you can apply it Learn about innovation accounting: methodologies for defining, experimenting, measuring, and communicating the true progress of innovation for new products, business models, or initiatives. Understand why not to scale, but instead to focus on significant customer interactions and passionate early adopters. Learn about the engines of growth, and identify what yours are. Learn how to transition between horizons to grow and transform your product. This lesson is for you because ... You're a business leader that wants to understand how to develop actionable metrics for measuring products in the innovation stage You're a team manager responsible for creating, measuring, and evaluating leading indicators of success for products or initiatives being developed by your team Prerequisites None Materials or downloads needed in advance None This lesson is taken from Lean Enterprise by Jez Humble, Joanne Molesky, and Barry O'Reilly.